Interferometry diagnostics of plasma channel of femtosecond filament. (November 2016) - Chizhov, P A; Bukin, V V; Garnov, S V
Abstract: Results of the electron density dynamics in the plasma channel of a femtosecond filament in air, nitrogen and argon from the moment of ionization up to hundreds of picoseconds after it are presented. Anisotropy of the refractive index was found, which is preceded and accompanied by ionization of the gas at the time of passage of high-intensity femtosecond laser pulse.